The comics world : comic books, graphic novels, and their publics - Woo, Benjamin; Stoll, Jeremy (University Press of Mississippi, 2021)
"Contributions by Bart Beaty, T. Keith Edmunds, Eike Exner, Christopher J. Galdieri, Ivan Lima Gomes, Charles Hatfield, Franny Howes, John A. Lent, Amy Louise Maynard, Shari Sabeti, Rob Salkowitz, Kalervo A. Sinervo, Jeremy Stoll, Valerie Wieskamp, Adriana Estrada Wilson, and Benjamin Woo The Comics World: Comic Books, Graphic Novels, and Their Publics is the first collection to explicitly examine the production, circulation, and reception of comics from a social-scientific point of view. Designed to promote interdisciplinary dialogue about theory and methods in comics studies, this volume draws on approaches from fields as diverse as sociology, political science, history, folklore, communication studies, and business, among others, to study the social life of comics and graphic novels. Taking the concept of a "comics world"-that is, the collection of people, roles, and institutions that "produce" comics as they are-as its organizing principle, the book asks readers to attend to the contexts that shape how comics move through societies and cultures. Each chapter explores a specific comics world or particular site where comics meet one of their publics, such as artists and creators; adaptors; critics and journalists; convention-goers; scanners; fans; and comics scholars themselves. Through their research, contributors demonstrate some of the ways that people participate in comics worlds and how the relationships created in these spaces can provide different perspectives on comics and comics studies. Moving beyond the page, The Comics World explores the complexity of the lived reality of the comics world: how comics and graphic novels matter to different people at different times, within a social space shared with others"--